Pembuatan Material Wood Plastic Composite Berbasis Limbah Pelepah Sawit Menggunakan Maleated Natural Rubber (Mnr) Sebagai Kompatibilizer - Akbar, Anif Aulia; Yelmida, Yelmida; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Natural rubber (NR) is one of the largest agricultural commodities in the world. But this potential is not balanced with satisfactory productivity. The purpose of this research was to study the effect of palm frond powder (SPS) / polyethylene (PE) ratio on physical properties, use Maleated Natural Rubber (MNR) as a compilizer and study the effect of MNR compatibility composition on the physical, mechanical properties of Wood Plastic Composite (WPC) palm fronds based. WPC samples were prepared by melted mixing method between palm fronds, polyethylene, MNR, and Minarex fibers at a temperature of 170oC and using the Internal Mixer. The size of the palm frond fiber used is 60-80 mesh. While the ratios of the weight ratio of SPS / PE are 60/40 and 70/30 and the addition of MNR is 0%, 1%, 3%, 5%, 7% and 9%. The test method includes mechanical properties which is tensile strength test while physical properties test includes density, water absorption, and thick development. The test results show that the best mechanical properties are produced at the SPS / PE (60/40) ratio, MNR (3%), with a tensile strength value of 23.164 MPa. While in physical properties, the best absorption is 0.477% in the ratio (60/40) with MNR (3%), the best thick development is 0.167% in the ratio (60/40) with MNR (3%) , and the highest density is 0.923% in the ratio (60/40) and MNR (5%). Keywords: Compatibilizer, maleated natural rubber, palm frond fiber, wood plastic composite